OBTAINING OF TUNGSTEN OXIDE NANOPARTICLES IN ULTRASONICALLY ASSISTED ELECTRIC DISCHARGE - Garibyan, Boris; Kohlert, Victoria (Revista Inclusiones, 2020)
In this study, plasma discharge in a liquid at intensive ultrasonic field above the cavitation threshold has been proven to be of great interest for initiation of various physical and chemical processes. In such surcharge, nanoparticles of tungsten oxide with controlled size and shape and narrow particle size distribution have been synthesized. Further exploration of synthesized nanoparticles has demonstrated that the factor of ultrasonic cavitation during the synthesis substantially affects physical and chemical characteristics of nanoparticles. Similar procedure might be effective for compounds of tungsten and rare-earth elements.